A game theoretic analysis of tactics in the phase of reception attack in volleyball - Hirotsu, N.; Ito, M.; Miyaji, C.; Hamano, K.; Taguchi, A. (International Journal of Computer Science in Sport, 2010)
In this paper, we analyze tactical conflicts between attacking formations and blocking formations in the phase of reception attack in volleyball, using a zerosum game model. In this model, we categorize the attacking formations into 9 patterns which consist of 3 moving patterns of forward players and 3 positions (right, center and left) from which the ball can be spiked. We also categorize the blocking formations into 3 formations: "spread", "bunch" and "dedicate". The conflicts are formulated as a zero-sum game by tabulating these formations, and analyzed by calculating the equilibrium points together with the value of the game. Following this formulation we have developed a game analysis system with Visual Basic programming code for solving the game. The solution gives us minimax strategies with the ratio of successful blocks. Here, we try an application of game theoretic analysis, using the empirical data taken from an intercollegiate women's league in 2004. We estimate the values of the game in the matches, and illustrate a possible improvement in terms of the allocation of attacking and blocking formations used in the matches from the macro-view of game theoretic analysis. This approach could hopefully provide a new standpoint of the analysis of real volleyball matches.